FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU BERBAHAYA (UNSAFE ACTION) PADA BAGIAN UNIT INTAKE PT.INDONESIA POWER UNIT BISNIS PEMBANGKITAN (UBP) SEMARANG 2011 - Dwi Noor Maulidhasari; MG Catur Yuantari; Nurjanah Nurjanah (Dian Nuswantoro Semarang, 2011)
Background: The main causes of workplace accidents are unsafe action 80% and the rest is unsafe condition. There are three phases that can lead to unsafe action namely management phase, working environment phase, and individual phase from the workers themselves. The result to unsafe action in workplace is the occurrence of workplace accidents that could effect the company and the workers themselves. The aim of this research is to examine some factors related to unsafe action on intake unit in PT. Indonesia Power UBP Semarang.Method: This is an analytical research by using survey method and cross sectional study approach. The numbers of samples are 30 employees at the Intake Unit. The statistic analysis used Pearson Product Moment and Rank Spearmen, to examine correlation between independent variables and dependent variables.Result: Statistical analysis result found that there are no relations between age (p value 0,135), education degree (p value 0,051), convenience in wearing personal protective equipment (p value 0,416) and experience of working accidents (p value 0,559) with unsafe action and there are relations between occupational health and safety knowledge (p value 0,000), attitude toward personal protective equipments (p value 0,001) and working group norm (p value 0,025) with unsafe action. The company should to prevent unsafe action by provide counseling and training on occupational accidents, safe behavior in the workplace and the importance of the use of personal protective equipment in the workplace.Keywords : unsafe action, workplace